Pergeseran Paradigma Hukum - K. A Bukhori (Medina-te : Jurnal Studi Islam, 2018)
Positivists may declare that metaphysics (transcendental) is dead, but now it is logical positivism that first died. It is remarkable that the era of Muslim, Jewish and Christian theist thinkers is now again engaged in a vast exploration of the idea of "God's hypothesis." This paper will try to describe the law and spiritualism. The study of law here is meant to describe law or law through the approach of historical perspective, namely in the era of positivism that gave birth to modern law in liberal society. At such times spiritual values which include: moral ethics and religion are not in place so that modern law experiences a spiritual crisis. In its development, there emerged a positivist critical thinking movement which sought to escape and sue positivist thought. Positivis boleh saja mengumumkan bahwa metafisika (transcendental) sudah mati, akan tetapi kini justru positivisme logislah yang duluan mati. Sangat menarik perhatian bahwa era pemikir teisme dari Muslim, Yahudi dan Kristen kini kembali terlibat dalam eksplorasi yang sangat luas terhadap gagasan “hipotesis Tuhan”. Tulisan ini akan mencoba menggambarkan hukum dan spiritualisme. Kajian hukum di sini dimaksudkan untuk menggambarkan hukum atau ilmu hukum melalui pendekatan perspektif historis, yakni pada era positivisme yang melahirkan hukum modern pada masyarakat liberal. Pada saat semacam itu nilai-nilai spiritual yang meliputi: etika moral dan agama tidak mendapat tempat sehingga hukum modern mengalami krisis spiritual. Dalam perkembangannya kemudian muncul gerakan pemikiran kritis yang post positivis yang berupaya untuk melepaskan diri dan menggugat pemikiran positivis.